Eksklusivitas Ijtima’ Ulama Komisi Fatwa MUI tentang Salam Lintas Agama Perspektif Maqashid al-Syari’ah dan Moderasi Beragama - Harun, Mohd Taufik; Diwanda, Bayu; Firdaus, Zulkifli; Hendri, Hendri (KIPS Institute Bukittinggi, 2025)
This study analyzed Ijtima’ Komisi Fatwa (se-Indonesia) VIII number: 02/Ijtima’ Ulama/VIII/2024 issued by the Indonesian Ulema Council (Majelis Ulama Indonesia) concerning the prohibition of interfaith greetings from the perspectives of maqasid al-sharia and religious moderation in Indonesia. The fatwa generated diverse societal responses due to its implications for tolerance and interreligious relations in a pluralistic context. Supporters viewed the prohibition as a preventive measure to protect Islamic faith (hifzh al-din) and to maintain clear theological boundaries, while critics considered it insufficiently contextualized and potentially detrimental to social harmony and interfaith dialogue. This study employed a qualitative library research approach by examining official MUI fatwa documents, classical and contemporary Islamic legal theories, and relevant academic literature. Data were analyzed using content analysis and a descriptive-analytical method. The findings showed that the fatwa was grounded in the principle of hifzh al-din as a primary objective of Islamic law, aiming to prevent syncretism and ritual imitation. However, a comprehensive maqasid sharia approach required the fatwa to also consider social harmony and mutual respect among religious communities. The study concluded that the fatwa sought to balance doctrinal integrity with social coexistence, thereby contributing to the discourse on religious moderation in Indonesia.